Styrene Monomer Levels in Polystyrene-Packed Dairy Products from the Market versus Simulated Migration Testing - Valeria Guazzotti; Veronika Hendrich; Anita Gruner; Angela Störmer; Frank Welle (Foods, 2023)
In view of the fact that a specific migration limit (SML) is to be established in the near future for styrene monomer in plastic food contact materials (FCMs), data on the dietary exposure of the European population, as well as sensitive and reliable analytical methodologies to implement compliance testing, are needed. The properties of the substance styrene as well as those of styrenic polymers pose challenges for analysts and their design of experimental migration tests. The aim of this study was to assess the level of styrene in polystyrene (PS)-packed dairy products from supermarkets and compare these values with the results from simulated migration testing. In addition to the conventional food simulant and test conditions described in Regulation (EU) No 10/2011 for refrigerated dairy products (50% ethanol for 10 days at 40 °C), milder simulants and test conditions (10% ethanol and 20% ethanol for 10 days at 40 °C and 20 °C) were investigated. Styrene levels in the investigated foods ranged from 2.8 µg/kg to 22.4 µg/kg. The use of 50% ethanol causes interactions with PS (swelling) that do not occur with dairy products and leads to highly exaggerated migration results. In contrast, testing PS for 10 days at 40 °C with 10% and 20% ethanol leads to higher styrene migration levels than found in real food, which are still conservative but far less extreme. Testing PS for 10 days at 20 °C leads to styrene migration levels that are more comparable to, but still overestimate, those found in real food products stored under refrigerated conditions.